Accounting harmonization in the matters of transparency in the supreme court of justice in the state of Sonora - Castellanos Trujillo, Silvino (Universidad de Sonora, 2018)
The theme of this study is to know of the accounting harmonization in the matters of accounting related to transparency; is a theme that with the pass of time has been implementing in some states, cities, beings and organizations; yet with the time that has passed since the creation of this Law, there hasn’t been a significative advance on the process for the harmonization and implementation of the systems to operate and give results to the law. On this investigation we are looking to obtain the knowledge on the theme of transparency in the fields that build up to it as to make a detailed report about its evaluation, control and its development. The evaluation will be done by the ISAF (Instituto Superior de Auditoria y Fiscalizacion) together with the CEAC (Consejo Estatal de Armonizacion Contable) with the use of an informatic platform denominated SEVAC (Sistema de Evaluación de Armonización Contable). On this investigation it will be around the three powers of the executive, in this case on the Power of  the Attorney of the State of Sonora, which was selected to form part of the pilot test and count with information for the analysis and reviewing its results. From the information that was analyzed, it was validated that in some sections that form the transparency, they present problems keeping the objectives on the second, third and fourth trimester of 2017. This concludes that the public entities are still lacking on the structure or the appropriate systems for the harmonization and the norms that places the LGCG (Ley General de Contabilidad Gubernamental).